A potential ant-hemiptera-plant mutualism on Lorostemon coelhoi (Clusiaceae) in the Brazilian Amazon - Silvia Larissa FERREIRA-SILVA; Michael G. J. HOPKINS; Thiago M. MOUZINHO; Rosaly A. ROCHA; Lucas C. MARINHO (Acta Amazonica)
ABSTRACT Interactions among organisms are important in ecosystem functioning and relevant for the management and conservation of species. Here we report the first record of a potential ant-hemiptera-plant mutualism on Lorostemon coelhoi (Clusiaceae) in Manaus, Amazonas state, Brazil. Our observations on five trees indicated that the presence of hemiptera nymphs diverted ants from damaging flower buds while looking for nectar, because the nymphs secrete honeydew, which is collected by the ants instead. Trees without hemiptera nymphs produced less fruit due to damage to flower buds by ants. The observation suggests the occurrence of a tripartite mutualistic interaction among these organisms that represent three trophic levels. The absence of hemiptera nymphs could directly affect the reproductive success of the plant by increasing the predation of flower buds by ants. The interaction deserves further investigation.